Faith, fear, and disclosure: Exploring serodiscordant relationships in Indonesia’s Muslim society - Ridwan, Eka Sari; Tanasugarn, Chanuantong; Benjakul, Sarunya; Kengganpanich, Mondha; Mohammadnezhad, Masoud (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: In Indonesia’s Muslim society, serodiscordant couples navigate a complex web of faith, fear, and stigma. While HIV care efforts have advanced, understanding how religious beliefs and emotional responses shape disclosure remains limited. Objective: This study aimed to explore the lived experiences of serodiscordant couples in South Sulawesi, Indonesia, with a focus on how faith, fear, and gender roles influence HIV understanding and disclosure practices. Methods: A qualitative, phenomenological approach was employed, involving 34 participants who participated in in-depth interviews and focus group discussions conducted between February and May 2019. Data were thematically analyzed to capture emotional, cultural, and relational dimensions of HIV disclosure. Results: Two main themes emerged. (1) Faith and Fear: Navigating HIV Understanding, which includes knowledge of HIV, emotional responses to an HIV diagnosis, the role of religious teachings in shaping health decisions, and the fear of social exclusion; and (2) HIV Status Disclosure and Its Complexities, highlighting motivations for disclosure, barriers to openness, and the personal impact of revealing one’s HIV status to a partner. Disclosure was often delayed or mediated by third parties, driven by fear of rejection, shame, and limited communication skills. Conclusion: The findings revealed the dual role of faith as both a support and a barrier, and the complex interplay of gender dynamics in disclosure decisions. Community nurses in Indonesia’s primary health care settings should then play a critical role in HIV prevention by providing culturally sensitive, Islamic-faith-based counseling, gender-responsive disclosure support, and collaboration with peer support groups to foster trust, reduce stigma, and improve adherence.